Sex chromosome changes in leukemia: cytogenetics and molecular aspects. Issue 3 (16th March 2018) - Shahrabi, Saeid; Khodadi, Elahe; Saba, Fakhredin; Shahjahani, Mohammad; Saki, Najmaldin
ABSTRACT: Background and objective: Sex chromosome loss (SCL) can occur in older men as a physiological phenomenon or as an acquired abnormality in leukemia. Loss of chromosome Y and loss of chromosome X are acquired disorders that are mainly observed in patients over 80 years as well as in myeloid and lymphoid malignancies. In this review, we examine the cytogenetic and molecular changes of sex chromosomes in leukemia. Methods: Relevant English language literature were searched and retrieved from PubMed search engine (1990–2016). The following keywords were used: 'Sex chromosomes', 'Leukemia' and 'Cytogenetics'. Results: The loss of tumor suppressor genes along with these chromosomal abnormalities in the majority of malignant cells in bone marrow (BM) has raised the question whether this is an age-related phenomenon or has occurred as a result of clonal abnormality. On the other hand, the presence of these chromosomal abnormalities in a number of genetic diseases associated with leukemia leads to progression of malignancy, and their role in peripheral blood stem cell transplantation confirm the finding that these chromosomal abnormalities can play an important role in clonal abnormality. Conclusion: The presence of these abnormalities can cause genetic instability in BM and result in the development of a malignant clone and progression of the disease. In addition, the evaluation of SCL together with the genes involved in these chromosomes can contribute to predict the disease prognosis as well as monitoring of malignancy.